The Use of Integrated 5Es of Inquiring-Based Learning and Gamification to Improve Grade 8 Student Science Learning Achievement - Pannarai Bantaokul; Titiworada Polyiem (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the effectiveness of integrated 5Es of inquiring-based learning and gamification on grade 8 science learning achievement and to study students’ attitudes toward science learning with the integration of the two principles. The participants were 40 eighth-grade students from a Thai public school. They were chosen using a cluster sampling technique with their section as the primary criterion for selection. The instruments were learning management designed using the integration of the 5Es of inquiry-based learning and gamification, a learning achievement test, and an attitude survey questionnaire. Data analysis employed both descriptive statistics (e.g., percentage, mean score, standard deviation) and comparative statistics (e.g., paired-samples t-test, and effectiveness index with the determining criterion of 80/80). The study’s findings show that combining the learning activities of the 5Es of inquiry-based learning with the elements of gamification resulted in the development of participants’ science learning achievement. Additionally, it offered an engaging and motivating learning experience which led to positive attitudes toward science learning.